On the growth mechanism of the primary silicon particle in a hypereutectic Al-20 wt%Si alloy using synchrotron X-ray tomography. (5th January 2018) - Wang, J.; Guo, Z.; Song, J.L.; Hu, W.X.; Li, J.C.; Xiong, S.M.
Abstract: The 3-D morphology of the primary silicon particle (PSP) in a hypereutectic Al-20 wt%Si alloy was characterized using synchrotron X-ray tomography. It was found that the most probable particle morphology always had a shape factor of 0.85, indicating either a regular octahedron or a twinned shape with a / h  = 2.5 ( a was the edge length and h was the distance between the outer surface and the {111} plane). A growth transition model was then developed to describe the growth mechanism for the PSPs. It is believed that both octahedral and twinned shapes are a transition from a so-called facetted growth unit, which has a morphology of just half octahedron and evolves from a spherical nucleation. Further growth of the silicon particles can lead to the formation of hollow hoppers due to the mismatch of the growth velocity along different directions. Graphical abstract: Highlights: Morphologies of primary silicon particles are characterized and analyzed statistically, with the most shape factor of 0.85. Morphological feature between octahedral and twinned shapes presents similarity and reveals the potential growth transition. Twinning influences the basic facet growth that leads to the octahedral shape and promotes the formation of twinned shape.